2021
DOI: 10.3389/fphar.2021.699193
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Environmental Toxins-Induced Cardiotoxicity and Protective Potential of Natural Products

Abstract: Humans are unconsciously exposed to environmental toxins including heavy metals as well as various pesticides, which have deleterious effects on human health. Accumulating studies pointed out that exposure to environmental toxins was associated with various cardiopathologic effects. This review summarizes the main mechanisms of cardiotoxicity induced by environmental toxins (cadmium, arsenic and pesticides) and discusses the potential preventive effects of natural products. These findings will provide a theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 139 publications
(151 reference statements)
0
13
0
Order By: Relevance
“…An example is a fungus-derived fingolimod drug, which the FDA approved for the treatment of multiple sclerosis [ 345 , 346 ]. One of the major advantages of NPs in drug discovery is that they confer multiple “targets” by targeting more than one signaling pathway [ 347 ]. In addition, most NPs showed beneficial effects through their antioxidant, anti-inflammatory, and anti-apoptotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…An example is a fungus-derived fingolimod drug, which the FDA approved for the treatment of multiple sclerosis [ 345 , 346 ]. One of the major advantages of NPs in drug discovery is that they confer multiple “targets” by targeting more than one signaling pathway [ 347 ]. In addition, most NPs showed beneficial effects through their antioxidant, anti-inflammatory, and anti-apoptotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanisms of drug toxicity are heavily studied in animal hearts, the real effect and mechanisms in human cardiomyocytes are less well understood [ 36 ], which prompted the development of HTS for mitochondrial toxicants in human-relevant platforms. In addition to drug-induced mitochondrial toxicity, accumulating studies have pointed out that environmental toxins, including various pesticides and heavy metals, may also induce cardiotoxicity [ 401 , 402 ]. Hence, HTS may be useful in applications beyond the regular drug discovery pipeline.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Fetuin-A has been proposed as an endogenous inhibitor of pathological mineralization or calcification. [22][23][24] An essential role for fetuin-A in attenuating injury and infection-elicited inflammatory responses has been well described. 25,26 Studies have shown that fetuin-A at high concentration remarkably inhibits endotoxin-induced release of proinflammatory mediators, that is, TNF, IL-1, and nitric oxide in macrophage cultures, signifying anti-inflammatory potential of fetuin-A.…”
Section: Introductionmentioning
confidence: 99%
“…The intense release of inflammatory mediators elicits the generation of reactive oxygen species and causes tissue damage 22 . In sepsis‐induced cardiotoxicity, the cardiomyocyte oxidative stress reaction has been considered a hallmark and further trigger of endogenous antioxidant activity, as well as exogenous administration of antioxidant agents, has been shown to confer significant cardioprotection 23 . Therefore, attenuating inflammation and oxidative stress along with improvement in myocardial injury is considered the best potential therapeutic strategy for sepsis‐induced cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%